9x-2.3x-3=0

Simple and best practice solution for 9x-2.3x-3=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-2.3x-3=0 equation:


Simplifying
9x + -2.3x + -3 = 0

Reorder the terms:
-3 + 9x + -2.3x = 0

Combine like terms: 9x + -2.3x = 6.7x
-3 + 6.7x = 0

Solving
-3 + 6.7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 6.7x = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 6.7x = 0 + 3
6.7x = 0 + 3

Combine like terms: 0 + 3 = 3
6.7x = 3

Divide each side by '6.7'.
x = 0.447761194

Simplifying
x = 0.447761194

See similar equations:

| 9.7-m=2.8 | | 9-.5x=2 | | 6(x+1)=-18 | | 9-3x=-6x+3 | | 9x+6=3(2-x) | | 5x+2+5x+1=30 | | 6-5x=-x-2 | | x+5*3=36 | | -3(3x-7)=5(3x+1) | | 3(3x-7)=5(3x+1) | | 3(3x+6)=135 | | 8(2x+9)=120 | | .66x-4=-1 | | 6y+6=y-2 | | 1g(x+7)+1g(3x+1)=2 | | (-2)=4x+2 | | (x-3)*7=70 | | 0.05x=150 | | .66x-4=1 | | -4x+9x-(-4)=12x-5-(-10) | | 4y(5y-8)+24y= | | (x-10)*4=24 | | 2(4x-5)=12 | | x^2+2logX+94.3=0 | | (x+5)*6=54 | | (-3)=x^2-5 | | 3x-11+7x=51 | | x^2+lnX+92.3=0 | | n-(2n-1)=5-2(n-1) | | 12000(7+x)=108000 | | -12-5-6-(-25)= | | X-3.51=1.9 |

Equations solver categories